The Role of PTUN Procedural Law in Protecting Citizens' Rights Against Decisions of State Administrative Officials - Moh. Imam Gusthomi; Farrel Ardan Rinaldi; Marlina Dewi Setiani (Universitas Negeri Semarang, 2024)
This study aims to analyze the role of the State Administrative Court Procedure Law (PTUN) in protecting citizens' rights against decisions of state administrative officials that are considered detrimental. In the context of a state of law, PTUN functions as a control mechanism against actions of administrative officials that are not in accordance with the law. The research method used is a qualitative approach, with data collection through literature studies, and analysis of PTUN decision documents. The results of the study indicate that PTUN plays an important role in upholding the principles of a state of law and providing legal protection for citizens. However, there are still challenges in its implementation, such as the slow trial process, lack of public understanding of PTUN procedures, and limited access to legal aid. To overcome these challenges, an increase in the number of judges, broader legal education for the public, and better access to legal aid services are needed. In conclusion, PTUN procedural law plays a vital role in ensuring that decisions of state administrative officials can be tested and legally accounted for, thus providing effective protection for citizens.